How do macroeconomic variables and financial inclusion affect financial stability in Indonesia? - Anindyntha, Firdha Aksari; Fuddin, Muhammad Khoirul (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Financial stability is a crucial indicator of the financial sector's health, reflecting the system's resilience or vulnerability to crises. This study investigates the impact of macroeconomic variables and financial inclusion on financial stability in Indonesia, utilizing quarterly data from the first quarter of 2012 to the fourth quarter of 2021. Employing the Vector Error Correction Model (VECM), the research examines the influences of these factors in both the short and long term. The findings reveal that macroeconomic variables and financial inclusion significantly affect financial stability in Indonesia across both time frames. Specifically, inflation emerges as a critical factor influencing financial stability in the long term, while interest rates play a pivotal role in the short term. Moreover, financial inclusion, represented by the public's use of banking products and third-party funds relative to Gross Domestic Product (GDP), impacts financial stability both in the long and short term. Conversely, financial inclusion, measured by credit to GDP, exhibits only short-term effects on financial stability. The results underscore the importance of careful consideration by the central bank when formulating monetary policy, particularly regarding interest rate adjustments, due to their immediate impact on financial system stability. Over the long term, maintaining control over inflation rates is imperative to safeguard financial stability. Furthermore, financial institutions, in their role of fostering financial inclusion by distributing credit, must balance the quality of credit with its quantity to avoid negative impacts on the financial system's stability. This study contributes valuable insights for policymakers and financial institutions aiming to bolster Indonesia's financial stability through prudent macroeconomic management and the strategic implementation of financial inclusion initiatives.